Aerobic fitness level and its association with short-term memory and sustained attention among university students - Ng, Kit Foh; Muhamad, Ayu Suzailiana; Garry, Kuan (Faculty of Sports Science and Recreation, 2024)
Memory and sustained attention are critical cognitive functions that significantly impact academic performance. Numerous studies have demonstrated that regular exercise can improve both shortterm memory and sustained attention. However, to date, the association between aerobic fitness level and short-term memory and sustained attention among university students has not been extensively explored. Hence, the present study was carried out using a cross-sectional study design. A total of 38 participants (N=38) were recruited among university students. After obtaining their informed consent, participants’ height, weight, and body mass index (BMI) were recorded. In addition, participants performed the digit span test to measure their short-term memory and the digit vigilance test to measure their sustained attention. A 20-m shuttle run was also carried out, and the data obtained from the shuttle run was used to calculate their estimated maximal oxygen uptake. All the data obtained were analysed using descriptive statistics and the Pearson correlation test (SPSS version 28). Results showed that participants had a normal BMI (22.28 ± 4.03 kg/m²). Majority (36.84%) of the female participants had a very poor aerobic fitness level (27.19 ± 4.71 ml/kg/min), and majority (15.79%) of the male participants had a poor aerobic fitness level (37.07 ± 7.45 ml/kg/min). Regarding the correlation analysis, there were no significant correlations (p>0.05) between aerobic fitness level and short-term memory and sustained attention. In conclusion, the present study found that short-term memory and sustained attention were not affected by aerobic fitness level. However, further studies may address the limitations highlighted in the present study.